Decision-making: a laboratory-based case study in conceptual design - Maurice Girod (2001)
The engineering design process may be seen as a series of interrelated operations that are driven by decisions: each operation is carried out as the consequence of an associated decision. Hence, an effective design process relies heavily upon effective decision-making. As a consequence, supporting decision-making may be a significant means for achieving design process improvements. This thesis concentrates on how to support selection-type decision-making in conceptual engineering design. [Continues.]